PHASED DEVELOPMENT OF COMPETENCIES THROUGH BIM TECHNOLOGY-BASED PROJECT WORKS - N. B. Kurbanova (Next Scientists Conferences, 2025)
This article analyzes the step-by-step development of students’ professional competencies through project work based on Building Information Modeling (BIM) technologies. At each stage of the design process, students progressively enhance their skills in modeling, engineering thinking, technical documentation, and teamwork. The findings demonstrate the effective integration of BIM technologies into the educational process and their significant role in improving students’ qualifications.